Use of Adipose Stem Cells Against Hypertrophic Scarring or Keloid - Chen, Hongbo; Hou, Kai; Wu, Yiping; Liu, Zeming (Frontiers in Cell and Developmental Biology, 2022)
Hypertrophic scars or keloid form as part of the wound healing reaction process, and its formation mechanism is complex and diverse, involving multi-stage synergistic action of multiple cells and factors. Adipose stem cells (ASCs) have become an emerging approach for the treatment of many diseases, including hypertrophic scarring or keloid, owing to their various advantages and potential. Herein, we analyzed the molecular mechanism of hypertrophic scar or keloid formation and explored the role and prospects of stem cell therapy, in the treatment of this condition.